Snort IDS and IPS toolkit - Beale, Jay; Baker, Andrew R.; Esler, Joel (Jay Beale's open source security series, 2007)
This all new book covering the brand new Snort version 2.6 from members of the Snort developers team. This fully integrated book, CD, and Web toolkit covers everything from packet inspection to optimizing Snort for speed to using the most advanced features of Snort to defend even the largest and most congested enterprise networks. Leading Snort experts Brian Caswell, Andrew Baker, and Jay Beale analyze traffic from